Assessment of the enhanced weathering potential of different silicate minerals to improve soil quality and sequester CO2 - te Pas, Emily E. E. M.; Hagens, Mathilde; Comans, Rob N. J. (Frontiers in Climate, 2023)
Enhanced weathering is a negative emission technology that involves the spread of crushed silicate minerals and rocks on land and water. When applied to agricultural soils, the resulting increase in soil pH and release of nutrients may co-benefit plant productivity. Silicate minerals and rocks differ in their enhanced weathering potential, i.e. their potential for both carbon dioxide (CO2) sequestration and soil quality improvements. However, studies comparing silicate minerals and rocks for this dual potential are lacking. Therefore, we compared the enhanced weathering potential of olivine (Mg2SiO4), basalt, wollastonite (CaSiO3), and two minerals that are novel in this context, anorthite (CaAl2Si2O8) and albite (NaAlSi3O8). A down-flow soil column experiment was designed allowing for measurements on soils and leachate, and calculations of organic and inorganic carbon budgets. Our results showed comparatively high CO2 capture by enhanced wollastonite and olivine weathering. Furthermore, CO2 capture per m2 specific surface area indicated potential for enhanced anorthite and albite weathering. Calculated carbon budgets showed that most treatments produced net CO2 emissions from soils, likely related to the short duration of this experiment. All silicates generally improved soil quality, with soil nickel contents remaining below contamination limits. However, nickel concentrations in leachates from olivine-amended soils exceeded the groundwater threshold value, stressing the importance of monitoring nickel leaching. We found a relatively high enhanced weathering potential for wollastonite, while the potential for olivine may be constrained by nickel leaching. The promising results for anorthite and albite indicate the need to further quantify their enhanced weathering potential.